Alfabetização financeira sob a perspectiva da ruralidade feminina no interior do Ceará - Reis, Maria Vanessa Silva dos (2023)
Financial illiteracy presents itself as an aggravating factor present in several contexts, with negative implications arising not only from low knowledge, but also also of financially negative behaviors. Such implications take on proportions more expressive when related to the female gender and in rural regions, where, Historically, there are individuals with asymmetric access to information. In this sense, the Women present, in studies carried out worldwide, the lowest rates of financial literacy, being less likely to plan than men. This study aims to measure the level of financial literacy of rural women living in the municipality of Capistrano – CE. Data collection took place through the application of questionnaires, adopting financial knowledge and financial behavior as proxies, considering how analysis methodology the statistical grouping technique. Such analysis allowed the formation of three groups: Low, Medium and High Level of Financial Literacy (BNAF, MNAF, and ANAF). The results demonstrated that the rural women surveyed have a low level of of financial literacy, and it is necessary to consider them relevant for the formulation of strategies or public policies focused on solving this problem. In view of the gap existing in this field of study, we seek to encourage the development of research future projects with a focus on other rural spaces, especially those aimed at women, allowing, thus, to trace the level of Financial Literacy of rural women